Interconnected of Islamic Education Goals From The Perspective of Al Singkili - Kirana Fatikha Dina; Hafizha Sitta Imana; Moh. Faizin (Al-Bustan: Jurnal Pendidikan Islam, 2026)
The integration of spiritual, moral, intellectual, and social dimensions represents a fundamental objective of Islamic education. However, many contemporary educational systems tend to prioritize cognitive achievement while neglecting the ethical and spiritual formation of learners. This condition creates a gap between knowledge acquisition and character development in Islamic education. Classical Muslim scholars provide valuable insights to address this issue, including the educational thought of Abdurrauf Al-Singkili, a prominent seventeenth-century scholar from Aceh. This study aims to examine the interconnected goals of Islamic education from Al-Singkili’s perspective. The research employs a qualitative library research method through textual analysis of Al-Singkili’s works and relevant contemporary literature on Islamic educational philosophy. The findings reveal that Islamic education in Al-Singkili’s perspective is built upon an integrated framework consisting of spiritual foundations, moral formation, intellectual development, and social responsibility. The novelty of this research lies in reconstructing Al-Singkili’s educational thought into a holistic conceptual model that emphasizes the interconnectedness of educational goals in Islamic education.